Implementation of an Integrated E-Learning Module for Academic Summarization in English for Academic Purposes - Aris Rakhmadi; Yanti Haryanti (ABDIMASTEK, 2025)
This study aims to develop and implement an integrated e-learning module to enhance academic summarization skills in English for students at Universitas Muhammadiyah Surakarta (UMS). The module was designed to support English for Academic Purposes (EAP) learning and was integrated into regular courses. Through a combination of online and face-to-face learning, the module covered four key areas: summary organization, grammatical accuracy, academic vocabulary, and summarization techniques. The implementation involved a series of workshops and guided practice sessions, supported by self-directed learning through an e-learning platform. Quantitative evaluation was conducted using the English Proficiency Exam (EPE) and the Computerized Assessment System (CAS) across three student groups, with assessments administered on three platforms: traditional, Schoology, and OpenLearning. The results showed that students using the Schoology platform achieved the highest average EPE score (422.99). In contrast, CAS results were comparable across platforms (3.20 for the traditional group, 3.16 for Schoology, and 3.15 for OpenLearning). These findings indicate that the e-learning module is efficacious in improving academic summarization skills and can be sustainably implemented to support academic literacy at UMS.